Optimization of Green Building-Based Facade Design Using Value Engineering Methods in The Construction of Hospital Buildings - Kurniawan, Rizky; Susetyo, Budi (JURUSAN TEKNIK SIPIL, 2024)
Sustainable construction is a way for the construction industry to achieve sustainable development by considering social, economic, environmental and cultural issues. Generally, in every commercial building, the largest energy consuming equipment is air conditioning equipment, including hospital buildings, which is influenced by the design concept of the building facade surface. so this research was created to optimize green building-based building facade designs through heat transfer values on building wall facades or Overall Thermal Transfer Value (OTTV) which refers to SNI 6389:2011 concerning Energy Conservation of Building Envelopes using value engineering methods. The results show that the use of 310 Wp Solar Panels, blue green Stopsol Glass, Aluminum Composite Panels (ACP), Mortar Plaster Walls, Wheatershield Paint and is better at reducing heat with the lowest OTTV value of 34.16 Wh/m2 and provides optimal electricity cost savings of 18% at the end of the material life cycle.